Aceitabilidade e viabilidade tecnológica da elaboração de dois produtos de abacate ‘Hass' - Daiuto, Érica Regina [UNESP]; Simon, Juliana Wagner [UNESP]; Vieites, Rogério Lopes [UNESP]; Carvalho, Lídia Raquel de [UNESP]; Russo, Viviane Citadini [UNESP] (My University, 2012)
The avocado possesses appreciable nutritious characteristics. The objective of this research was to evaluate the paste and guacamole avocado acceptability and stability, conserved under low temperature, as well as the technological viability of the e labo ra t ion o f the se p rodu c t s . I t wa s eva lua ted f ru i t physico chemical characterization, yeld and color. The paste and guacamole were conditioned in packings polyetileno+nylon with vacuous being analyzed in the day of elaboration of the product (T0), to the 3 and 7 days under refrigeration, 15 and 30 under freezing, 3 and 7 after sample freezing thaw stored by 30 days and maintained under refrigeration. In the paste and guacamole it was evaluated the sensorial analyses, coloration and microbiology. The fruit presented pulp percentage of 58.71% in relation to the peel and pit that can have other technological uses. The pulp presented high content of lipids (28.2%). The sensorial evaluation showed that the two products were well accepted. The paste presented superior notes for the evaluated sensorial parameters in the refrigerated and freezing stored sample, however, after freezing thaw it happens oil liberation depreciating the aspect of the product. The coloration stayed stable during the storage period and superior values of brightness were verified for the paste. The two products were microbiological stable.

O abacate possui características nutritivas apreciáveis. O objetivo desta pesquisa foi avaliar a aceitabilidade eestabilidade da pasta de abacate e do guacamole, conservados pelo frio, assim como a viabilidade tecnológicada elaboração destes produtos. Foi realizada caracterização físico-química do fruto, rendimento e cor. A pasta eo guacamole foram acondicionadas à vácuo em embalagens polietileno+nylon sendo analisadas no dia deelaboração do produto (T0), aos 3 e 7 dias sob refrigeração, 15 e 30 sob congelamento, 3 e 7 apósdescongelamento de amostra armazenada por 30 dias e mantidas sob refrigeração. Na pasta e guacamoleforam realizadas análise de pH, acidez, sensorial, coloração e microbiologia. O fruto apresentou porcentagemde polpa de 58,71% em relação à casca e caroço, destacando-se o alto teor de lipídios (28,2%). A avaliaçãosensorial mostrou que os dois produtos foram bem aceitos. A pasta apresentou notas superiores para os parâmetros sensoriais avaliados nas amostras armazenadas refrigeradas ou congeladas, no entanto, após descongelamento ocorre liberação de óleo depreciando o aspecto do produto. A coloração se manteve estável nos produtos durante o período de armazenamento e valores de luminosidade superiores foram verificados para a pasta. Os dois produtos apresentaram estabilidade microbiológica.
Acceptability and technological viability production of two products of Hass avocado
Keywords: Persea americana Mill.; Guacamole; Paste; Refrigeration; Freezing; Freezing thaw; Persea americana Mill.; Guacamole; Pasta; Refrigeração; Congelamento; Descongelamento